Peran Kewirausahaan Sosial dalam Pemberdayaan Masyarakat: Tiga Cerita dari Kutai Timur - Denny Riezki Pratama (Universitas Padjadjaran, 2019)
Corporate Social Responsibility (CSR) and community development initiatives grow rapidly in recent years. It’s an act of a business ethics by taking part in efforts to achieve sustainable development goals (SDGs). It does not have economic value per se, but also social, cultural and political by involving local agent and existing cultural institutions which in turn catalyse the emergence and the redefinition of local social-political movement. This study discusses the emergence of local agent and their significant roles as social entrepreneur in the community development program initiated by Kaltim Prima Coal (KPC) in East Kalimantan province. This study employs qualitative method. Primary data were gathered from interviews and participant-observations, while secondary data were gathered from company reports and company internal presentation materials. The main qualitative data are short stories of three social entrepreneurs live in the mining areas who network with CSR and community development program of PT. Kaltim Prima Coal. This study suggests that social entrepreneurs are the key success of community development program, because they have the capability to foster members of their community to be innovative and creative, as well seize their opportunity for empowerment and to increase community members participation in development. The social entrepreneur have a strong bonding with local culture even though they are not native of their locality. In some cases, social entrepreneurs initiate the local socio-political movement and they do not merely play their role as social broker.